Response to nuclear and radiological terrorism - Voica, Dan-Radu; Kibaroglu, Mustafa (NATO science for peace and security series. E, Human and societal dynamics, 2011)
This book presents the results of the workshop Response to Nuclear and Radiological Terrorism, organized by the NATO Center of Excellence - Defence Against Terrorism (COE-DAT) in Ankara, Turkey, January 2010, under the sponsorship of the Science for Peace and Security Programme. This international workshop brought together academics, experts and military professionals to discuss and exchange views on the current threat from terrorist organizations which may attempt to use nuclear or radiological devices to achieve their goals. The workshop, and this book, also address the measures that international, regional and national organizations must implement in order to mitigate these threats, as well as the eventual management of the consequences in the event that such a device should be successfully exploited. The workshop consisted of six panels: What is Nuclear Terrorism?; Assessing the Threat of Nuclear Materials in Terror; How to Prevent Nuclear and Radiological Terrorist Attacks; International Cooperation on Preventing Acts of Nuclear/Radiological Terrorism and Future Trends and lastly; Concepts in Defence Against Nuclear Terrorism. These were supported by 18 lecturers from various institutions around the world. The arguments and insights of the authors whose essays are collected here mean that this book will be of great interest to all those involved in dealing with the potential threat of nuclear or radiological terrorist attacks and their consequences.